RANCANG BANGUN APLIKASI TRACER STUDY BERBASIS WEBSITE PADA UNIVERSITAS DINAMIKA - Jamali, Nashir; Amelia, Tan; Hariadi, Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
One indicator of a good education system is the system used to measure the quality of its output. The method used by universities to obtain feedback from graduates is a tracer study. Tracer studies are aimed at graduates and graduate/company users. Dinamika University has been conducting a tracer study since 2016 using an online system. However, the system is only used for filling out graduate questionnaires, while filling out graduate user questionnaires is still using the conventional system. Also, in the online tracer study system, the list of questions made is still in a static form so that it cannot be changed at any time according to instructions from the Higher Education. Based on these problems, a graduate tracking system is needed that can be used to fill out questionnaires for graduates and graduate users, and can add and change questions as needed. The tracer study method is used as a reference in carrying out the graduate tracing process to obtain graduate data which allows Dinamika University to obtain information on the education and learning process and becomes the basis for curriculum planning.